Upgrading museum experience: Insights into offline visitor perceptions through social media trends - Biao Gao; Shuangshuang Yu (Elsevier, 2024)
With the rise of the experience economy, visitor experiences and feedback have become central to improving museum services. To enhance their appeal, understanding visitors' real experiences is key. This study, based on online reviews of museums in Jiangxi Province from April 2020 to May 2023 on platforms like Dianping and Ctrip, employs high-frequency keyword analysis, topic analysis, semantic networks, and sentiment analysis to deeply explore visitors' offline experiences. While most visitors provided positive feedback, criticisms were also raised concerning exhibit content, service attitude, and interactive programs. These online feedbacks offer valuable insights, aiding us in understanding and enhancing the offline service experience in museums. This research provides a unique perspective for other museums and cultural institutions, aiming to optimize offline visitor experiences through online social media trends.